The Effectiveness Analysis and Strategy Exploration of Homestay Industry on Rural Revitalization of China - Xiong, Yihan (BCP Business & Management, 2022)
The homestay industry has been developing rapidly in recent years. It has become the pillar industry of rural economics to some extent, and the concept of rural revitalization is becoming more and more popular in China. Therefore, it is necessary to fathom the current situations in the homestay industry and find problems and feasible refinements. This paper mainly adopts two research methods, interview and literature research. By reviewing findings and conclusions from the previous studies and interviewing homestay owners and employees, the author points out several problems of the existing homestay industry, including applying stale developing approaches mechanically, being incompatible with the local environment, and lacking in cooperation with local governments. Also, this article discusses the crux of these problems. It provides possible solutions to help homestay owners better attract target customers and expand the market. The expansion of the thriving homestay industry gives back incentives to the local economy.